Obesity and Remission Rates in Japanese Patients With Rheumatoid Arthritis Requiring Anti-Tumor Necrosis Factor Alpha Therapy - Kenji YAMAZAKI,; Etsuji SUZUKI,; Ryuhei ISHIHARA,; Toshiaki MIYAMOTO, (Archives of Rheumatology, 2020)
Objectives: This study aims to determine if obesity is a risk factor for a poor response to anti-tumor necrosis factor alpha (anti-TNFα) therapy in Japanese patients with rheumatoid arthritis (RA) using the appropriate body mass index (BMI) cut-off points for Asian populations. Patients and methods: This retrospective cohort study evaluated 382 outpatients with RA (98 males, 284 females; mean age 54.2 years; range, 18 to 84 years) who had received anti-TNFα therapy between May 2009 and July 2017. Patients were classified according to BMI at baseline as follows: <18.5 kg/m2 (underweight), 18.5-23.0 kg/m2 (normal weight), 23.0-27.5 kg/m2 (overweight), and ≥27.5 kg/m2 (obese). The response variable was defined as Simplified Disease Activity Index (SDAI) remission after 12 months. We estimated odds ratios (ORs) and their 95% confidence intervals (CIs) for poor response to the therapy. Results: After 87 patients were excluded, 183 (62.0%) of 295 had reached remission at the 12-month follow-up. Compared with normal-weight patients, the multivariate OR for poor response of obese patients was 2.2 (95% CI: 0.5-9.4). Adjusting for the baseline SDAI score, the corresponding OR was 1.8 (0.4-7.6). Conclusion: We found no statistically significant association between obesity and poor response to anti-TNFα therapy in Japanese patients with RA. Because this may partly be due to the limited statistical power of our study, further research is warranted to examine the possible effect modification across countries.